The interaction of the general anesthetic etomidate with the γ-aminobutyric acid type A receptor is influenced by a single amino acid - Belelli, Delia (The National Academy of Sciences of the USA, 1997)
The γ-aminobutyric acid type A (GABA(A)) receptor is a transmitter-gated ion channel mediating the majority of fast inhibitory synaptic transmission within the brain. The receptor is a pentameric assembly of subunits drawn from multiple classes (α(1–6), β(1–3), γ(1–3), δ(1), and ɛ(1)). Positive allosteric modulation of GABA(A) receptor activity by general anesthetics represents one logical mechanism for central nervous system depression. The ability of the intravenous general anesthetic etomidate to modulate and activate GABA(A) receptors is uniquely dependent upon the β subunit subtype present within the receptor. Receptors containing β(2)- or β(3)-, but not β(1) subunits, are highly sensitive to the agent. Here, chimeric β(1)/β(2) subunits coexpressed in Xenopus laevis oocytes with human α(6) and γ(2) subunits identified a region distal to the extracellular N-terminal domain as a determinant of the selectivity of etomidate. The mutation of an amino acid (Asn-289) present within the channel domain of the β(3) subunit to Ser (the homologous residue in β(1)), strongly suppressed the GABA-modulatory and GABA-mimetic effects of etomidate. The replacement of the β(1) subunit Ser-290 by Asn produced the converse effect. When applied intracellularly to mouse L(tk−) cells stably expressing the α(6)β(3)γ(2) subunit combination, etomidate was inert. Hence, the effects of a clinically utilized general anesthetic upon a physiologically relevant target protein are dramatically influenced by a single amino acid. Together with the lack of effect of intracellular etomidate, the data argue against a unitary, lipid-based theory of anesthesia.